Reference left atrial dimensions and volumes by steady state free precession cardiovascular magnetic resonance - Maceira, Alicia M (BioMed Central, 2010)
BACKGROUND: Left atrial (LA) size is related to cardiovascular morbidity and mortality. Cardiovascular magnetic resonance (CMR) provides high quality images of the left atrium with high temporal resolution steady state free precession (SSFP) cine sequences. We used SSFP cines to define normal ranges for LA volumes and dimensions relative to gender, age and body surface area (BSA), and examine the relative value of 2D atrial imaging techniques in patients. For definition of normal ranges of LA volume we studied 120 healthy subjects after careful exclusion of cardiovascular abnormality (60 men, 60 women; 20 subjects per age decile from 20 to 80 years). Data were generated from 3-dimensional modeling, including tracking of the atrioventricular ring motion and time-volume curves analysis. For definition of the best 2D images-derived predictors of LA enlargement, we studied 120 patients (60 men, 60 women; age range 20 to 80 years) with a clinical indication for CMR. RESULTS: In the healthy subjects, age was associated with LA 4-chamber transverse and 3-chamber anteroposterior diameters, but not with LA volume. Gender was an independent predictor of most absolute LA dimensions and volume, but following normalization to BSA, some associations became non-significant. CMR normal ranges were modeled and are tabled for clinical use with normalization, where appropriate, for BSA and gender and display of parameter variation with age. The best 2D predictors of LA volume were the 2-chamber area and 3-chamber area (both r = 0.90, p < 0.001). CONCLUSIONS: These CMR data show that LA dimensions and volume in healthy, individuals vary significantly by BSA, with lesser effects of age and gender.